2004
DOI: 10.1002/lt.20244
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of combined orthotopic liver transplantation and coronary artery bypass grafting

Abstract: Advanced coronary artery disease (CAD) is increasingly common in patients awaiting orthotopic liver transplantation (OLT). Unfortunately, in patients whose coronary artery anatomy is not amenable to angioplasty, coronary artery bypass grafting (CABG) alone may precipitate hepatic decompensation. Thus, combined liver transplant and coronary artery bypass grafting (CABG-OLT) may be required to effectively treat both conditions. Clinical records were analyzed for 5 CABG-OLT procedures at a single institution. Ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…17,18 While there can be no doubt that improved surgical and anesthetic techniques contribute to decreased blood transfusion requirements, 14 the use of high doses of aprotinin, as administered in our patients, mandates specific comment.…”
Section: Discussionmentioning
confidence: 87%
“…17,18 While there can be no doubt that improved surgical and anesthetic techniques contribute to decreased blood transfusion requirements, 14 the use of high doses of aprotinin, as administered in our patients, mandates specific comment.…”
Section: Discussionmentioning
confidence: 87%
“…Combined CABG and OLT has emerged as a solution for this trouble. [5,6] Axelrod et al [2] reported five patients undergoing combined CABG-OLT operations. One-year survival was 80% with no perioperative death.…”
Section: Discussionmentioning
confidence: 99%
“…However, this accompanies risk for hepatic deterioration after cardiopulmonary bypass (CPB). [2] In this manner, combined CABG and OLT were performed to treat both diseases. [3] Therefore, in this article, we report consecutive CABG and OLT operations in less than 24 hours as an alternative approach.…”
mentioning
confidence: 99%
“…Other noncardiac procedures such as mastectomy [28,29], thymectomy [30], thyroid surgery [31], nephrectomy [32,33], renal [34] and liver transplantation [35,36], and other vascular surgeries [37,38] have also been performed. In general terms, the preference for either a staged or combined procedure is determined by specific features of each combination.…”
Section: Discussionmentioning
confidence: 99%